Neurobehavioural and biochemical responses associated with exposure to binary waterborne mixtures of zinc and nickel in rats (2020)
Environmental and occupational exposure to metal mixtures due to various geogenic and anthropogenic ac- tivities poses a health threat to exposed organisms. The outcome of systemic interactions of metals is a topical area of research because it may cause either synergistic or antagonistic effect. The present study investigated the impact of co-exposure to environmentally relevant concentrations of waterborne nickel (75 and 150 pg NiCl 2L-1) and zinc (100 and 200pg ZnC^L-1) mixtures on neurobehavioural performance of rats. Locomotor, motor and exploratory activities were evaluated using video-tracking software during trial in a novel arena and thereafter, biochemical and histological analyses were performed using the cerebrum, cerebellum and liver. Results indicated that zinc significantly (p < 0.05) abated the nickel-induced locomotor and motor deficits as well as improved the exploratory activity of exposed rats as verified by track plots and heat map analyses. Moreover, zinc mitigated nickel-mediated decrease in acetylcholinesterase activity, elevation in biomarkers of liver damage, levels of reactive oxygen and nitrogen species as well as lipid peroxidation in the exposed rats when compared with control. Additionally, nickel mediated decrease in antioxidant enzyme activities as well as the increase in tumour necrosis factor alpha, interleukin-1 beta and caspase-3 activity were markedly abrogated in the cerebrum, cerebellum and liver of rats co-exposed to nickel and zinc. Histological and histomorphome- trical analyses evinced that zinc abated nickel-mediated neurohepatic degeneration as well as quantitative re- duction in the widest diameter of the Purkinje cells and the densities of viable granule cell layer of dentate gyrus, pyramidal neurones of cornu ammonis 3 and cortical neurons in the exposed rats. Taken together, zinc abrogated nickel-induced neurohepatic damage via suppression of oxido-inflammatory stress and caspase-3 activation in rats.